Preparation of catalyst from natural montmorillonite mineral and its application in the synthesis of carbon nanosphere - Ochirkhuyag, Altantuya; Rentsennorov, Ulambayar; Batmunkh, Davaabal; Gendenjamts, Oyun-Erdene; Odbaatar, Enkhtur; Tsend-Ayush, Tserendagva; Temuujin, Jadambaa (Mongolian Journal of Chemistry, 2022)
In developed countries, nanoparticles derived from natural minerals and high-purity chemicals both are widely studied, while in developing countries like Mongolia, the natural minerals-based nanoparticles have more interest because of the low production cost and applicability of domestic natural minerals for their production. For the synthesis of natural mineral-based nanomaterials, it is important first to define the chemical composition and physical structure of local minerals and their possible processing route. We employed an environmentally friendly alkaline leaching procedure to recover silica from the clay mineral at 90°C for 24 hours. We applied an organic surfactant (CTAB) and a simple coprecipitation approach to form iron-doped silica nanoparticles. Consequently, we used iron-doped silica nanoparticles as a substrate and catalyst for the synthesis of carbon nanosphere at 750 °C for 1 hour in an argon and acetylene gas atmosphere. As a result, vast quantities of superhydrophobic carbon nanospheres (CNS) were obtained. The physicochemical properties of nanosilica substrate, non-functionalized carbon nanosphere, and functionalized carbon nanosphere (CNS) samples were characterized using XRD, XRF, SEM, EDS, TEM, and FTIR spectrometer. Iron-doped mineral-derived nanosilica particles demonstrated high catalytic efficiency and the potential to produce a large amount of value-added carbon nanospheres. Superhydrophobic CNS can be used in a variety of applications, particularly drug delivery; however, to use CNS in both aqueous and non-aqueous media, the superhydrophobic properties of CNS can be modified using different oxidizers. The changes in hydrophobicity of the CNS were examined and suggested possible oxidizing agents.